Investigations on flexural characteristics of functionally graded alumina and alumina-titania ceramic composite coatings. (15th March 2011) - Rajakumar, Sundaram; Vijayaraghavan, L.; Mayuram, M.M.; Krishnamurthy, R.
Detonation-gun (D-gun) sprayed alumina-based ceramic composites as mono-layered and functionally graded coatings (FGC) are evaluated. The coatings are subjected to three-point bending test to assess their flexural response. The results show that among the depositions, monolayer alumina-titania deposition exhibits better flexure characteristics compared to the functionally graded coatings.